Non-covalent Interaction With SUMO Enhances the Activity of Human Cytomegalovirus Protein IE1 - Tripathi, Vasvi; Chatterjee, Kiran Sankar; Das, Ranabir (Frontiers in Cell and Developmental Biology, 2021)
Viruses interact with the host cellular pathways to optimize cellular conditions for replication. The Human Cytomegalovirus (HCMV) Immediate-Early protein 1 (IE1) is the first viral protein to express during infection. It is a multifunctional and conditionally essential protein for HCMV infection. SUMO signaling regulates several cellular pathways that are also targets of IE1. Consequently, IE1 exploits SUMO signaling to regulate these pathways. The covalent interaction of IE1 and SUMO (IE1-SUMOylation) is well studied. However, the non-covalent interactions between SUMO and IE1 are unknown. We report two SUMO-Interacting Motifs (SIMs) in IE1, one at the end of the core domain and another in the C-terminal domain. NMR titrations showed that IE1-SIMs bind to SUMO1 but not SUMO2. Two critical functions of IE1 are inhibition of SUMOylation of Promyelocytic leukemia protein (PML) and transactivation of viral promoters. Although the non-covalent interaction of IE1 and SUMO is not involved in the inhibition of PML SUMOylation, it contributes to the transactivation activity. The transactivation activity of IE1 was previously correlated to its ability to inhibit PML SUMOylation. Our results suggest that transactivation and inhibition of PML SUMOylation are independent activities of IE1.